Digital learning preferences of Arabic-speaking older immigrants in Canada: a qualitative case study - Au, Alesia; Siddiqi, Hesham; Sayadi, Ghada; Zhao, Tianqi; Kleib, Manal; Tong, Hongmei; Salma, Jordana (My University, 2024)
The COVID-19 pandemic has highlighted the importance of digital inclusion for equitable and healthy aging. Older immigrants experience unique needs and challenges in using information and communication technologies compared to other older adults. Despite the proliferation of digital learning programs for older adults, there is minimal evidence of digital literacy learning needs and strategies relevant to older immigrants. The aim of this study is to explore learning approaches and digital engagement amongst Arabic-speaking older immigrants. This community-based qualitative descriptive study used co-designed group digital learning sessions. Two organizations supporting local ethnocultural communities in a municipality in Alberta, Canada recruited 31 older immigrants who spoke Arabic, Farsi, and Kurdish. Data collection included semi-structured interviews, focus groups, and observations of digital learning sessions. A total of seventeen learning sessions were completed with nineteen participants each attending five to six sessions. Findings highlight the iterative nature of the program sessions, the importance of catering to participants’ interests, the relevance of peer support, and language, sensory and digital variability barriers to learning. Digital literacy programs for immigrant older adults should adjust for language learning needs, maintain a flexible approach, tailor lessons to individual needs, foster social support, and address external factors such as limited digital access and transportation barriers.
Keywords: adult learning; adult literacy; aging (individuals); digital literacy; educational needs; electronic learning; focus groups; immigrants; Semitic languages